Training on Prompt-Based Artificial Intelligence (AI) to Enhance Students’ Scientific Papers: Pengabdian - Sulviana Sulviana; Muthmainnah Mursidin; Jusmaniar Nonci; Rizka Indahyanti; Sitti Nurjannah; Muhammad Chairil Imran; Sri Fatimah Rahmatillah; Citra Prasiska Puspita Tohamba (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Although writing scientific papers requires critical thinking and mastery of academic language, many students still struggle with coherence, logical structure, and proper citation. However, advances in artificial intelligence (AI), particularly prompt-based generative language models, offer new opportunities to support academic writing. The training included a presentation of the material and practical exercises, followed by questionnaires and interviews to explore students’ perceptions. The results indicated that the moderate and targeted use of AI, especially during the planning and revision stages, improved the clarity of the academic language and the cohesion between paragraphs. AI helped students overcome psychological barriers to writing, increasing their motivation without raising ethical concerns related to academic integrity and overreliance on AI-generated content. Overall, the community service team concludes that prompt-based AI can effectively enhance students’ scientific papers when used with critical reflection, guidance from lecturers, and strong ethical awareness.